Self Healing Dalam Tasawuf Perspektif Imam Al-Ghazali Dalam Kitab Minhajul Abidin - Mega Windi Antika; Wijaya; Yulian Rama Pri Handiki (CV. ITTC INDONESIA, 2024)
Healing on social media is currently becoming popular, because the healing that circulates on social media is interpreted as traveling and culinary activities, etc., this form of healing will actually give rise to new problems, namely a hedonistic lifestyle, this is a problem in the meaning and implementation process This research aims to understand the concept of self-healing according to Imam Al-Ghazali in self-healing and reveal the truth of the meaning of self-healing through the concept of repentance in order to achieve happiness and perfection in life with the value of worship. The method used in this research is qualitative research (Library Research) with a Content research model Analysis (content analysis), through the Sufism approach. Conclusion: Repentance as self-healing functions as a tool for cleaning black spots in the heart, strengthening thoughts and feelings, encouraging human development and potential, so the true meaning of healing is returning to the Creator, apart from getting rewards, it can reduce mental disorders and gain peace of mind, by rknow and carry out the requirements for repentance and know the dangers of delaying repentance.